Anterior horn cell dysfunction in Alzheimer's disease. Issue 4 (April 1982) - Thomas, M; Ballantyne, J P; Hansen, S; Weir, A I; Doyle, D
Abstract : Electrophysiological studies were undertaken on 29 patients with Alzheimer's Disease. A reduction in the number of functioning motor units was found in the extensor digitorum brevis muscle. The electrophysiological parameters of the motor unit potentials were increased compared to control values. Four of seven muscle biopsies showed abnormalities ranging from mild to severe. The results suggest dysfunction in the lower motor neurone in this disease.